Analisis Dampak dari Pelaksanaan Female Genital Mutilation (FGM) Terhadap Kesehatan Reproduksi : A Literature Review - Romadlona, Nohan Arum; Azzahra, Alifia Rizqyandra; Setyawati, Avita Ayu; Permatasari, Karina Putri; Azizah, Naila Aufa; Azzahro, Nur Fauziah; Nazia, Safira Intan (Prosiding Seminar Kesehatan Nasional Sexophone, 2024)
Female genital mutilation is a partial cutting of the entire clitoris and even the labia minora and majora. In Indonesia, based on Riskesdas data in 2018, there was a prevalence of 30.6% of the incidence of female genital mutilation, which means that 1 in 3 children have experienced female genital mutilation. This is contrary in the medical field, where FGM has a negative impact on reproductive health. The purpose of this study was to analyze the impact of FGM on reproductive health. This study used a method in the form of a literature review by conducting a review of articles on the theme of female genital mutilation associated with reproductive health. The articles used in this study are 12 with a publication year of 2014-2024, the language used is Indonesian. From the analysis conducted, it was found that there are short-term and long-term impacts in the implementation of female genital mutilation on reproductive health, short-term impacts include bleeding, tetanus, and rotting wounds, while long-term impacts include prolonged pain, difficulty during menstruation, urinary tract infections, incontinence, and complications during childbirth.